Estimation Of Time Parameter Proportionality Ratios In Large Catchments: Case Study Of The Modder-Riet River Catchment, South Africa - Allnutt, C.E.; Gericke, O.J.; Pietersen, J.P.J. (Journal of Flood Risk Management Volume 13, Issue 3 e12628, 2020)
Catchment response time parameters, for example, the time of concentration (TC), lag time (TL), and time to peak (TP) are fundamental to event-based design flood estimation in ungauged catchments. Hydrological literature often fails to clearly differentiate between the seven different time parameter definitions interchangeably used in practice and consequently, proportionality ratios are commonly applied. This article aims to investigate and establish the suitability of the currently recommended time parameter definitions and proportionality ratios for small catchments in larger sub-catchments exceeding 50 km2 by using an automated hyetograph–hydrograph analysis tool. The time parameter estimates proved to be highly variable, but the average time parameter proportionality ratios proved to be less significant and in all the sub-catchments, it was confirmed that the average proportionality ratios equal unity, that is, TC ≈ TL ≈ TP. Hence, the currently recommended TC:TL proportionality ratios of 1.417 and 1.667, are respectively not applicable at larger catchment levels. The establishment of unbiased empirical time parameter equations would remain an international challenge if the misinterpretation of the different time parameter definitions and use of incorrect time parameter proportionality ratios continue; hence, the results from this study, as well as others, should be considered for further investigation and/or implementation.
Article
Keywords: Catchment response time; Lag time; Runoff; Rainfall spatial distribution; South Africa; Time of concentration; Time to peak